Number theory seminar - Columbia University Number Theory Seminar (1992 : Columbia,New York); Columbia University number theory seminar Columbia, New York 1992 (Paris Societe Mathematique de France, 1995)
The papers cover sevral aspects of modern number theory including torsion of elliptic curves, rational points, arithmetic of function fields, zeta functions and motives.
Keywords: Number theory